A method for improving the stability of perovskite solar cells by carbonyl compounds

By introducing three-dimensional compounds with three carbonyl functional groups into the absorption layer of the perovskite solar cell, the problem of perovskite solar cell prone to phase change under room temperature conditions is solved, and its stability and photoelectric conversion efficiency are significantly improved.

CN117858590BActive Publication Date: 2025-04-08CHONGQING UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410078586.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-18
Publication Date
2025-04-08
Estimated Expiration
2044-01-18

AI Technical Summary

Technical Problem

Perovskite solar cells are prone to phase change under room temperature conditions, resulting in non-photoactive phase generation, reducing the photoelectric power conversion efficiency and limiting their commercial applications.

Method used

A three-dimensional compound with at least 3 carbonyl functional groups, such as 4,4',4"-nitrotribenzaldehyde, is introduced into the perovskite absorbing layer, to inhibit the formation of non-optical active phases and stabilize the optically active phase of the perovskite.

Benefits of technology

The stability and photoelectric conversion efficiency of perovskite solar cells are significantly improved, reaching a maximum of 24.6%, and the initial efficiency of more than 90% is maintained after 1000 hours of stability detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117858590B_ABST
    Figure CN117858590B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of optoelectronic materials, and specifically relates to a method for improving the stability of perovskite solar cells by using carbonyl compounds. The method introduces a three-dimensional compound having at least three carbonyl functional groups into a perovskite absorption layer to stabilize the photoactive phase of the perovskite, and the finally prepared perovskite solar cell can maintain more than 90% of the initial PCE after 1000 hours of testing, and XRD detection shows that the non-photoactive phase is significantly suppressed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photoelectric materials, and in particular relates to a method for improving the stability of perovskite solar cells by using carbonyl compounds. Background Art

[0002] In the global context of carbon neutrality, the development of photovoltaic power generation is conducive to energy conservation and emission reduction. Perovskite solar cells have the advantages of low preparation cost and high photoelectric power conversion efficiency. However, perovskites are prone to phase transition at room temperature and are prone to generate non-photoactive phases, which in turn results in low photoelectric power conversion efficiency, limiting the commercial application of perovskite solar cells. Therefore, it is of great significance to prepare high-stability perovskite solar cells under the condition of ensuring good performance of perovskite solar cells.

[0003] The Chinese patent with the publication number CN114914362A (20220816) and the invention name "A method for preparing an efficient and stable perovskite solar cell" discloses that a passivation defect additive is added to a perovskite precursor solution to prepare a perovskite light-absorbing layer. The small molecule structure of the passivation defect additive includes a carbonyl group, an amino group, a benzene ring, and a fluorine group. The patent aims to solve the problem that currently only a single functional group in many materials acts on perovskite, thereby reducing the service life of the device.

[0004] The Chinese patent with the publication number CN111223994A (20220614) and the invention name "A fully printed mesoscopic perovskite solar cell using carbonyl small molecules as additives and its preparation method" discloses that a carbonyl small molecule additive ethylene carbonate with a molar ratio of 6% is introduced into the perovskite precursor solution as a passivator and cross-linking agent for perovskite crystallization. The open circuit voltage of the perovskite solar cell finally prepared is 0.92V and the photoelectric conversion efficiency is 15.44%. However, the photoelectric conversion efficiency of existing perovskite solar cells has reached more than 20%, so the photoelectric conversion efficiency of the perovskite solar cell prepared by this patent strategy is not very high.

[0005] In summary, it is necessary to propose new methods and strategies to supplement the shortcomings of existing technologies. Summary of the invention

[0006] In view of this, the main purpose of the present invention is to provide a preparation method based on carbonyl compounds to improve the stability of perovskite solar cells. The specific technical scheme is as follows.

[0007] A method for preparing a high-stability perovskite solar cell based on a carbonyl compound, wherein a three-dimensional compound having at least three carbonyl functional groups is introduced into a perovskite absorption layer to suppress a non-optically active phase (stable optically active phase) in the perovskite, wherein the three-dimensional compound having at least three carbonyl functional groups is 4,4',4"-nitrotribenzaldehyde, and the molar concentration of the three-dimensional compound and lead iodide in the perovskite absorption layer is 0.3-6 mM:1-1.6 M.

[0008] The molecular formula of 4,4',4"-nitrotribenzaldehyde is C 21 H 15 NO3, a molecule with a three-dimensional structure and three carbonyl functional groups (-C=O), can react spatially with unreacted lead in perovskite, thereby stabilizing the crystal structure of perovskite.

[0009] Furthermore, the molar concentration of the 4,4',4"-nitrobenzaldehyde and the lead iodide in the perovskite absorption layer is 1 mM: 1 to 1.6 M.

[0010] Furthermore, the specific steps of the method are as follows:

[0011] S01: Cleaning the transparent conductive glass layer;

[0012] S02: preparing a 30% tin oxide solution with deionized water to form a water-dispersed solution, and then dropwise spin-coating the solution on the conductive glass layer to prepare a tin oxide electron transport layer;

[0013] S03: 0.3mM to 6mM 4,4',4"-nitrobenzaldehyde is mixed with 1 to 1.6M lead iodide mixed solution, and then the mixture is added dropwise to the tin oxide electron transport layer for spin coating to form a lead iodide film, and an organic ligand solution is further prepared, wherein the organic ligand solution comprises 0.02 to 0.06M methylammonium iodide, 0.10 to 0.30M methylammonium chloride and 0.4 to 0.7M formamidine hydroiodide, and the organic ligand solution is added dropwise to the lead iodide film for spin coating to prepare a perovskite layer;

[0014] S04: using isopropanol as solvent, preparing a 2-6 mg / mL phenethylammonium iodide solution and spin coating it on the perovskite layer to prepare a phenethylammonium iodide layer;

[0015] S05: Preparation of Spiro-OMeTAD hole transport layer;

[0016] S06: Evaporation of molybdenum oxide and silver electrodes.

[0017] Furthermore, the volume ratio of the 30% tin oxide solution to deionized water in S02 is 1:3 to 1:4.

[0018] Furthermore, the operation of forming the lead iodide film in S03 is spin coating at 1500-2000 rpm for 10-40 seconds and annealing at 70° C. for 0.5-3 minutes.

[0019] Furthermore, the operation of preparing the perovskite layer in S03 is to spin-coat at 1600-2300 rpm for 10-40 seconds, and anneal at 130-170° C. for 10-30 minutes at a relative humidity of 20-40%.

[0020] Further, a 60-90 mg / mL Spiro-OMeTAD solution is prepared in S05, and 20-40 μL of a 4-tert-butylpyridine solution and a 240-300 mg / mL lithium bis(trifluoromethanesulfonyl)imide solution are further added, and the solution is spin-coated on the phenethylammonium iodide layer at 2000-5000 rpm for 20-40 seconds.

[0021] Furthermore, in S06, 1 to 9 nm of molybdenum oxide and 100 to 160 nm of silver are evaporated.

[0022] The perovskite solar cell prepared by the above method has a light absorption layer of formamidinium-based perovskite.

[0023] Furthermore, the thickness of the formamidinium-based perovskite is in the range of 700 to 800 nm.

[0024] Beneficial technical effects

[0025] 1. The preparation method provided by the present invention only introduces compound molecules with at least 3 carbonyl groups and a three-dimensional spatial structure in the process of preparing the perovskite light absorption layer, which is used to stabilize the optically active phase of the perovskite, greatly improving the stability of the perovskite solar cell. It is achieved that the stability of the perovskite solar cell is improved by using only a compound with a single functional group. The perovskite solar cell prepared by the method of the present invention has a maximum photoelectric conversion efficiency of 24.6%, and can maintain more than 90% of the initial PCE after 1000h stability testing. XRD detection proves that the non-photoactive phase is significantly suppressed.

[0026] 2. The spatial three-dimensional structured molecules introduced by the method of the present invention can also passivate the internal defects of the perovskite solar cell and reduce non-radiative recombination to increase the open circuit voltage of the perovskite solar cell, and the optimal open circuit voltage is 1.7V. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.

[0028] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell prepared in Example 1 of the present invention;

[0029] Figure 2 The microstructure of the perovskite film prepared in Example 1 of the present invention (scale: 1 μm);

[0030] Figure 3 The microstructure of the perovskite film prepared in Example 4 of the present invention (scale: 1 μm);

[0031] Figure 4 XRD spectra of the perovskite films prepared in Examples 1 and 4 of the present invention;

[0032] Figure 5 The PCE spectra of the long-term operation stability of the perovskite solar cells prepared in Examples 1 and 4 of the present invention;

[0033] Figure 6 Voc spectra of the perovskite solar cells prepared in Examples 1 to 9 of the present invention;

[0034] Figure 7 This is a microstructure diagram of the perovskite film prepared in Example 4 of the present invention (scale: 1 μm).

[0035] Summary of reference numerals:

[0036] 101: ITO conductive glass layer, 102: electron transport layer, 103: perovskite light absorption layer, 104: hole transport layer, 105: molybdenum oxide layer, 106: silver electrode layer. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Herein "and / or" includes any and all combinations of one or more of the associated listed items.

[0039] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.

[0040] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0041] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.

[0042] In this specification, some embodiments may be disclosed in a format of being within a certain range. It should be understood that such description of "being within a certain range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values ​​within this range. For example, the range The description of should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6 etc., as well as individual numbers within this range, for example, 1, 2, 3, 4, 5, and 6. The above rules apply regardless of the breadth of the range.

[0043] Glossary

[0044] The "photoactive phase" in the present invention refers to the phase corresponding to the peak with 2theta of 13.9° in XRD, which is the photoactive phase in perovskite.

[0045] The “optically non-active phase” mentioned in the present invention refers to the phase corresponding to the peak with 2theta of 11.7° in XRD, which is the optically non-active phase in perovskite.

[0046] Example 1

[0047] This embodiment provides a method for preparing a perovskite solar cell, and the specific steps are as follows.

[0048] S01: Treating ITO conductive glass: Wash the ITO conductive glass with detergent, deionized water, acetone, and isopropyl alcohol for several times, and then use a UV ozone cleaner to clean the ITO conductive glass for 20 to 40 minutes.

[0049] S02: Preparation of tin oxide electron transport layer: 30% tin oxide dispersion is prepared into a water dispersion solution, deionized water is added to the 30% tin oxide solution and shaken, and the volume ratio of the 30% tin oxide solution to deionized water is 1:3 to 1:4. The prepared dispersion is dropped onto the cleaned ITO conductive glass, spin-coated at a speed of 2000 to 5000 rpm, and then annealed at 130 to 170°C for 20 to 40 minutes.

[0050] S03: Preparation of perovskite absorption layer: In an inert gas atmosphere, 1.0-1.6M lead iodide (pbI2) solution (DMF:DMSO volume ratio is 9:1) is added dropwise on the tin oxide electron transport layer, spin coated at 1500-2000 rpm for 10-40 seconds, and annealed at 70°C for 0.5-3 minutes; using isopropanol as solvent, 0.02-0.06M methyl ammonium iodide (MAI), 0.10-0.30M methyl ammonium chloride (MACl) and 0.4-0.7M formamidine hydroiodide (FAI) organic ligand solution is prepared; the above organic ligand solution is added dropwise on the annealed lead iodide film, and spin coated at 1600-2300 rpm for 10-40 seconds. Anneal at 130-170°C for 10-30 minutes at 20-40% relative humidity.

[0051] S04: preparing a phenethylammonium iodide layer: using isopropanol as a solvent, preparing a 2-6 mg / mL phenethylammonium iodide solution, and spin coating it on the perovskite layer at 3000-4000 rpm.

[0052] S05: Preparation of hole transport layer: Using chlorobenzene as solvent, prepare 60-90 mg / mL Spiro-OMeTAD solution, in addition, add 20-40 μL 4-tert-butylpyridine (TBP) solution to the solution, add 240-300 mg / mL lithium bistrifluoromethanesulfonyl imide (LiTFSI) solution using acetonitrile as solvent; add the mixed solution dropwise to the phenethylammonium iodide layer, spin-coat at 2000-5000 rpm for 20-40 seconds, and place in dry air for 10-36 hours.

[0053] S06: Vapor deposit 1 to 9 nm of molybdenum oxide and 100 to 160 nm of silver.

[0054] The structural schematic diagram of the perovskite solar cell prepared in this embodiment is shown in Figure 1 The microstructure of the perovskite film is shown in Figure 2As shown, the perovskite grains are small and there are holes on the surface.

[0055] Example 2

[0056] This embodiment provides another example of preparing a perovskite absorption layer

[0057] In an inert gas atmosphere, 0.3mM 4,4',4"-nitrobenzaldehyde and 1.0-1.6M lead iodide mixed solution (DMF:DMSO volume ratio is 9:1) are dripped on the tin oxide electron transport layer, spin-coated at 1500-2000 rpm for 10-40 seconds, and annealed at 70°C for 0.5-3 minutes; isopropanol is used as a solvent to prepare a mixed solution of 0.02-0.06M methylammonium iodide (MAI), 0.10-0.30M methylammonium chloride (MACl) and 0.4-0.7M formamidine hydroiodide (FAI); the mixed solvent is dripped on the annealed lead iodide film, and spin-coated at 1600-2300 rpm for 10-40 seconds. Annealing is performed at 130-170°C for 10-30 minutes at a relative humidity of 20-40%.

[0058] Example 3

[0059] This embodiment provides another example of preparing a perovskite absorption layer

[0060] In an inert gas atmosphere, a mixed solution of 0.6 mM 4,4',4"-nitrobenzaldehyde and 1.0-1.6 M lead iodide (DMF:DMSO volume ratio of 9:1) is added dropwise to the tin oxide electron transport layer, and the mixture is spin-coated at 1500-2000 rpm for 10-40 seconds, and annealed at 70°C for 0.5-3 minutes; a mixed solution of 0.02-0.06 M methyl ammonium iodide (MAI), 0.10-0.30 M methyl ammonium chloride (MACl) and 0.4-0.7 M formamidine hydroiodide (FAI) is prepared using isopropanol as a solvent; the mixed solvent is added dropwise to the annealed lead iodide film, and the mixture is spin-coated at 1600-2300 rpm for 10-40 seconds. The mixture is annealed at 130-170°C for 10-30 minutes at a relative humidity of 20-40%.

[0061] Example 4

[0062] This embodiment provides another example of preparing a perovskite absorption layer

[0063] In an inert gas atmosphere, a mixed solution of 1mM 4,4',4"-nitrobenzaldehyde and 1.0-1.6M lead iodide (DMF:DMSO volume ratio is 9:1) is added dropwise to the tin oxide electron transport layer, and the mixture is spin-coated at 1500-2000 rpm for 10-40 seconds, and annealed at 70°C for 0.5-3 minutes; a mixed solution of 0.02-0.06M methylammonium iodide (MAI), 0.10-0.30M methylammonium chloride (MACl) and 0.4-0.7M formamidine hydroiodide (FAI) is prepared using isopropanol as a solvent; the mixed solvent is added dropwise to the annealed lead iodide film, and the mixture is spin-coated at 1600-2300 rpm for 10-40 seconds. The mixture is annealed at 130-170°C for 10-30 minutes at a relative humidity of 20-40%.

[0064] The perovskite solar cell prepared by the method of this embodiment is characterized in structure, and its microstructure is shown in the figure below: Figure 3 As shown. It shows obvious perovskite structural characteristics, but compared with the perovskite solar cell prepared by the method of Example 1 (without adding 4,4',4"-nitrogen tribenzaldehyde), the grain characteristics of this embodiment are obviously larger, and the contact between the crystals is closer.

[0065] Example 5

[0066] This embodiment provides another example of preparing a perovskite absorption layer

[0067] In an inert gas atmosphere, a mixed solution of 2mM 4,4',4"-nitrobenzaldehyde and 1.0-1.6M lead iodide (DMF:DMSO volume ratio is 9:1) is added dropwise to the tin oxide electron transport layer, and the mixture is spin-coated at 1500-2000 rpm for 10-40 seconds, and annealed at 70°C for 0.5-3 minutes; a mixed solution of 0.02-0.06M methylammonium iodide (MAI), 0.10-0.30M methylammonium chloride (MACl) and 0.4-0.7M formamidine hydroiodide (FAI) is prepared using isopropanol as a solvent; the mixed solvent is added dropwise to the annealed lead iodide film, and the mixture is spin-coated at 1600-2300 rpm for 10-40 seconds. The mixture is annealed at 130-170°C for 10-30 minutes at a relative humidity of 20-40%.

[0068] Example 6

[0069] This embodiment provides another example of preparing a perovskite absorption layer

[0070] In an inert gas atmosphere, a mixed solution of 3mM 4,4',4"-nitrobenzaldehyde and 1.0-1.6M lead iodide (DMF:DMSO volume ratio of 9:1) is added dropwise to the tin oxide electron transport layer, and the mixture is spin-coated at 1500-2000 rpm for 10-40 seconds, and annealed at 70°C for 0.5-3 minutes; a mixed solution of 0.02-0.06M methylammonium iodide (MAI), 0.10-0.30M methylammonium chloride (MACl) and 0.4-0.7M formamidine hydroiodide (FAI) is prepared using isopropanol as a solvent; the mixed solvent is added dropwise to the annealed lead iodide film, and the mixture is spin-coated at 1600-2300 rpm for 10-40 seconds. The mixture is annealed at 130-170°C for 10-30 minutes at a relative humidity of 20-40%.

[0071] Example 7

[0072] This embodiment provides another example of preparing a perovskite absorption layer

[0073] In an inert gas atmosphere, a mixed solution of 4mM 4,4',4"-nitrobenzaldehyde and 1.0-1.6M lead iodide (DMF:DMSO volume ratio is 9:1) is dropped on the tin oxide electron transport layer, and the mixture is spin-coated at 1500-2000 rpm for 10-40 seconds, and annealed at 70°C for 0.5-3 minutes; a mixed solution of 0.02-0.06M methylammonium iodide (MAI), 0.10-0.30M methylammonium chloride (MACl) and 0.4-0.7M formamidine hydroiodide (FAI) is prepared using isopropanol as a solvent; the mixed solvent is dropped on the annealed lead iodide film, and the mixture is spin-coated at 1600-2300 rpm for 10-40 seconds. The mixture is annealed at 130-170°C for 10-30 minutes at a relative humidity of 20-40%.

[0074] Example 8

[0075] This embodiment provides another example of preparing a perovskite absorption layer

[0076] In an inert gas atmosphere, a mixed solution of 5mM 4,4',4"-nitrobenzaldehyde and 1.0-1.6M lead iodide (DMF:DMSO volume ratio is 9:1) is added dropwise to the tin oxide electron transport layer, and the mixture is spin-coated at 1500-2000 rpm for 10-40 seconds, and annealed at 70°C for 0.5-3 minutes; a mixed solution of 0.02-0.06M methylammonium iodide (MAI), 0.10-0.30M methylammonium chloride (MACl) and 0.4-0.7M formamidine hydroiodide (FAI) is prepared using isopropanol as a solvent; the mixed solvent is added dropwise to the annealed lead iodide film, and the mixture is spin-coated at 1600-2300 rpm for 10-40 seconds. The mixture is annealed at 130-170°C for 10-30 minutes at a relative humidity of 20-40%.

[0077] Example 9

[0078] This embodiment provides another example of preparing a perovskite absorption layer

[0079] In an inert gas atmosphere, a mixed solution of 6mM 4,4',4"-nitrobenzaldehyde and 1.0-1.6M lead iodide (DMF:DMSO volume ratio is 9:1) is added dropwise to the tin oxide electron transport layer, and the mixture is spin-coated at 1500-2000 rpm for 10-40 seconds, and annealed at 70°C for 0.5-3 minutes; a mixed solution of 0.02-0.06M methylammonium iodide (MAI), 0.10-0.30M methylammonium chloride (MACl) and 0.4-0.7M formamidine hydroiodide (FAI) is prepared using isopropanol as a solvent; the mixed solvent is added dropwise to the annealed lead iodide film, and the mixture is spin-coated at 1600-2300 rpm for 10-40 seconds. The mixture is annealed at 130-170°C for 10-30 minutes at a relative humidity of 20-40%.

[0080] Example 10

[0081] Results Characterization

[0082] Table 1 4,4',4"-nitrobenzaldehyde content in Examples 1-9

[0083]

[0084] The perovskite solar cell prepared according to the method of Example 2-9 has an electron transport layer of a tin oxide film with a thickness ranging from 40 to 60 nm; the perovskite light absorption layer is a formamidinium-based perovskite (FAPbI3) with a thickness ranging from 700 to 800 nm; the hole transport layer is Spiro-OMeTAD; the molybdenum oxide layer has a thickness ranging from 2 to 5 nm; and the silver electrode layer has a thickness ranging from 90 to 110 nm.

[0085] 1.XRD test

[0086] Experimental method: The prepared perovskite film was detected using ESCALAB 250Xi (Thermo Fisher).

[0087] Table 2 XRD test results

[0088]

[0089] 2. Long-term running stability test

[0090] Experimental method: The photocurrent density-voltage (JV) curves were measured using a solar simulator equipped with a 450W xenon lamp (Newport 6279NS) and a Keithley 2400 light source meter. The effective area of ​​the device tested was 0.08cm2 (Calibration mask). JV curve from -0.1 to 1.2 V (forward scan) or from 1.2 to -0.1 V (reverse scan), scan rate is 100 mV -1 Using a standard Si solar cell calibrated by the National Institute of Metrology (NIM), the light intensity was adjusted to AM 1.5G one sun (100mWcm -2 The prepared batteries were subjected to JV tests at 0, 100, 200, 400, 600, 800, and 1000 h, and the PCE was recorded.

[0091] Table 3 PCE results

[0092] 0h 100h 200h 400h 600h 800h 1000h Example 1 21.00 22.68 21.42 19.53 17.01 15.33 12.81 Example 4 22.80 24.65 23.96 22.96 21.95 21.35 20.90

[0093] The results showed that the perovskite solar cells containing 1mM 4,4',4"-nitrogen tribenzaldehyde can maintain more than 90% of the initial PCE after 1000 hours of testing. The PCE of the perovskite solar cells without adding 4,4',4"-nitrogen tribenzaldehyde was 61% of the initial after 1000 hours of testing.

[0094] 3. Open circuit voltage test of perovskite solar cells

[0095] Experimental method: During the measurement of the photocurrent density-voltage (JV) curve, under light, when the device is open circuit, that is, when the current passing through is zero, the voltage across the device is measured.

[0096] Table 4 Open circuit voltage of different perovskite solar cells

[0097] Content (mM) 0 0.3 0.6 1 2 3 4 5 6 <![CDATA[V OC (V)]]> 1.3 1.5 1.7 1.6 1.5 1.5 1.4 1.4 1.3

[0098] Conclusion: The perovskite solar cell with 1mM 4,4',4"-nitrotribenzaldehyde has the best open circuit voltage of 1.7V.

[0099] 4. Power conversion efficiency

[0100] In the process of photocurrent density-voltage (JV) curve measurement, the power conversion efficiency (PCE) is the ratio of the maximum output power Pmax of the device to the input power Pin of the incident light.

[0101] Table 5 Power conversion efficiency (PCE) of different embodiments

[0102] Example 1 2 3 4 5 6 7 8 9 10 PCE(%) 22.6 23.3 23.8 24.6 24.3 24.0 23.7 23.1 22.5 22.3

[0103] The perovskite solar cell containing 1 mM 4,4',4"-tribenzaldehyde has the best photoelectric conversion efficiency, which is 24.6%.

[0104] Example 10

[0105] Under an inert gas atmosphere, 3 mM of 4-butylbenzaldehyde (C 11 H 14 O) and 1.0-1.6M lead iodide mixed solution (DMF:DMSO volume ratio is 9:1) are added dropwise to the tin oxide electron transport layer, and spin coated at 1500-2000 rpm for 10-40 seconds, and annealed at 70°C for 0.5-3 minutes; using isopropanol as solvent, 0.02-0.06M methyl ammonium iodide (MAI), 0.10-0.30M methyl ammonium chloride (MACl) and 0.4-0.7M formamidine hydroiodide (FAI) organic ligand solution is prepared; the above organic ligand solution is added dropwise to the annealed lead iodide film, and spin coated at 1600-2300 rpm for 10-40 seconds. Annealed at 130-170°C for 10-30 minutes at 20-40% relative humidity. Figure 7 To add 4-butylbenzaldehyde (C 11 H 14 O) SEM microstructure image, in which holes can be seen on the surface of the perovskite and the crystals are small.

[0106] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A method for preparing a high-stability perovskite solar cell based on a carbonyl compound, characterized in that: The method introduces a three-dimensional compound having at least three carbonyl functional groups into the perovskite absorption layer to suppress the non-optically active phase in the perovskite, wherein the three-dimensional compound having at least three carbonyl functional groups is 4,4',4"-nitrobenzaldehyde, and the molar concentration ratio of the three-dimensional compound to the lead iodide in the perovskite absorption layer is 0.3-6 mM: 1-1.6 M.

2. The method according to claim 1, characterized in that The molar concentration ratio of the 4,4',4"-nitrobenzaldehyde to the lead iodide in the perovskite absorption layer is 1mM:1-1.6M.

3. The method according to claim 1, characterized in that The specific steps are as follows: S01: Cleaning the transparent conductive glass layer; S02: adding deionized water to a 30% tin oxide solution to prepare a water-dispersed solution, and then dropwise spin-coating the solution on the conductive glass layer to prepare a tin oxide electron transport layer; S03: adding a mixed solution of 0.3mM to 6mM 4,4',4"-nitrotribenzaldehyde and 1 to 1.6M lead iodide to the tin oxide electron transport layer by spin coating to form a lead iodide film, further preparing an organic ligand solution, the organic ligand solution comprising 0.02 to 0.06M methylammonium iodide, 0.10 to 0.30M methylammonium chloride and 0.4 to 0.7M formamidine hydroiodide, and adding the organic ligand solution to the lead iodide film by spin coating to prepare a perovskite layer; S04: using isopropanol as solvent, preparing a 2-6 mg / mL phenethylammonium iodide solution and spin coating it on the perovskite layer to prepare a phenethylammonium iodide layer; S05: Preparation of Spiro-OMeTAD hole transport layer; S06: Evaporation of molybdenum oxide and silver electrodes.

4. The method according to claim 3, characterized in that The volume ratio of 30% tin oxide solution to deionized water in S02 is 1:3 to 1:

4.

5. The method according to claim 3, characterized in that The operation of forming the lead iodide film in S03 is to spin-coat at a spin-coating speed of 1500 to 2000 rpm for 10 to 40 seconds and anneal at 70° C. for 0.5 to 3 minutes.

6. The method according to claim 3, characterized in that The operation of preparing the perovskite layer in S03 is to spin-coat at 1600-2300 rpm for 10-40 seconds, and anneal at 130-170° C. for 10-30 minutes at a relative humidity of 20-40%.

7. The method according to claim 3, characterized in that Prepare 60-90 mg / mL of Spiro-OMeTAD solution in S05, further add 20-40 μL of 4-tert-butylpyridine solution and 240-300 mg / mL of lithium bis(trifluoromethanesulfonyl)imide solution, and spin coat on the phenethylammonium iodide layer at 2000-5000 rpm for 20-40 seconds.

8. The method according to claim 3, characterized in that In S06, molybdenum oxide with a thickness of 1 to 9 nm and silver with a thickness of 100 to 160 nm are evaporated.

9. A perovskite solar cell prepared by the method according to any one of claims 1 to 8, characterized in that: The light absorption layer in the perovskite solar cell is formamidinium-based perovskite.

10. The perovskite solar cell according to claim 9, characterized in that: The thickness of the formamidinium-based perovskite is in the range of 700 to 800 nm.

Citation Information

Patent Citations

  • Preparation method of efficient and stable titanium ore solar cell

    CN114914362A

  • Non-fullerene electron transport material as well as synthesis method and application thereof

    CN109336852A

  • All-printed mesoscopic perovskite solar cell adopting carbonyl small molecules as additive and preparation method thereof

    CN111223994A